2003
DOI: 10.1083/jcb.200301080
|View full text |Cite
|
Sign up to set email alerts
|

Rho activation patterns after spinal cord injury and the role of activated Rho in apoptosis in the central nervous system

Abstract: Growth inhibitory proteins in the central nervous system (CNS) block axon growth and regeneration by signaling to Rho, an intracellular GTPase. It is not known how CNS trauma affects the expression and activation of RhoA. Here we detect GTP-bound RhoA in spinal cord homogenates and report that spinal cord injury (SCI) in both rats and mice activates RhoA over 10-fold in the absence of changes in RhoA expression. In situ Rho-GTP detection revealed that both neurons and glial cells showed Rho activation at SCI l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
316
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(333 citation statements)
references
References 62 publications
16
316
0
1
Order By: Relevance
“…However, in Schwann cells, endogenous RhoA was activated after stimulation with BDNF, whereas knockdown of p75 NTR inhibited this activation (Yamauchi et al, 2004). In spinal cord injury (SCI) model, blocking activation of Rho after SCI protects cells from p75 NTR -dependent apoptosis (Dubreuil et al, 2003). In our experiments, p75 NTR mimetic LM11A-31 stimulation led to inhibition of Rho GTPase in anti-cancer drug treated cells, supporting the notion that p75 NTR effects are context dependent.…”
Section: Discussionsupporting
confidence: 78%
“…However, in Schwann cells, endogenous RhoA was activated after stimulation with BDNF, whereas knockdown of p75 NTR inhibited this activation (Yamauchi et al, 2004). In spinal cord injury (SCI) model, blocking activation of Rho after SCI protects cells from p75 NTR -dependent apoptosis (Dubreuil et al, 2003). In our experiments, p75 NTR mimetic LM11A-31 stimulation led to inhibition of Rho GTPase in anti-cancer drug treated cells, supporting the notion that p75 NTR effects are context dependent.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the activation of Rho-A by myelin Nogo-A could be damaging for neurons after injury; blocking Rho-A activation after spinal cord injury protected the cells from p75 NTR -dependent apoptosis. 55 Similarly, the increase of retinal ganglion cell survival in Cnp-Cre þ / À xRtn4 flox/flox mice could be due to the reduction of Rho-A activation that we observed in axotomized retinae.…”
Section: Moreover Inflammation-inducing Agents Such As Zymosan or Pamentioning
confidence: 56%
“…This signal may counteract the Rap1 signal. It was reported that the application of the Rho antagonist C3-05 reduced the number of TUNEL-positive cells by B50% in both rats and mice with spinal cord injuries, 25 suggesting that Rho may be the signal responsible for cell death. Our preliminary data demonstrate that the application of Y-27632 -a Rho-kinase inhibitor -reduced the number of TUNEL-positive CGNs that were pretreated with TAT-Rap1 DN and then incubated with MAG-Fc (data not shown).…”
Section: Discussionmentioning
confidence: 99%